PREGNANCY ECTOPIC TINGO MARIA - Arauzo Chuco, Godofredo (2015)
It is unanimous acceptance that ectopic pregnancy is found most often in the fallopian tubes. In practice the terms of ectopic pregnancy and tubal pregnancy is used synonymously. The results of 39 ectopic pregnancies treated at the Hospital of Tingo Maria between January 10, 1971 to December 31, 1985 is investigated ectopic per 530 live births was found: the 53.84% were 15 to 29 years; 100% had pain, vaginal bleeding 94.87% and shock, 5.12%, was 12.82% diagnostic error: multiparas paid greater tribute (71.79%) presented symptoms before 9 weeks of pregnancy, 92.30%: as evidence of support diagnostic, culdocentesis and dosage of B-HCG mere qualitative immunoassay was used in addition to routine analysis; the salpinguestomía was used as a treatment in 94.87%. All the ectopic pregnancy is in the tubes. We had no maternal death. The frequency of ectopic pregnancy, in Tingo Maria Tingo Maria is reduced.